Lewis Acid–Base Adducts for Efficient and Stable Cesium‐Based Lead Iodide‐Rich Perovskite Solar Cells. Issue 12 (13th November 2022) - Lu, Hui; Li, Tong; Ma, Simin; Xue, Xiaoyang; Wen, Qian; Feng, Yajuan; Zhang, Xu; Zhang, Lu; Wu, Zhiqiang; Wang, Kang; Liu, Shengzhong (Frank)
Abstract: All‐inorganic cesium‐lead‐iodide (CsPbI3 Br3− x (2 < x < 3)) perovskite presents preeminent photovoltaic performance and chemical stability. Unfortunately, this kind of material suffers from phase transition to a nonperovskite phase under oxidative chemical stresses. Herein, the introduction of a low concentration of Lewis acid–base adducts (LABAs) is reported to synergistically reduce defect density, optimize interfacial energy alignment, and improve device stability of CsPbI2.75 Br0.24 Cl0.01 (CsPbTh3 ) solar cells. Both theoretical simulations and experimental measurements reveal that the noncoordinating anions, PF6 −, as a Lewis base can more effectively bind with undercoordinated Pb 2+ to passivate iodide vacancy defects than the BF4 − and absorbed I −, and thus the point defects are well suppressed. In addition, N ‐propyl‐methyl piperidinium (NPMP + ) is selected to assemble with PF6 − in CsPbTh3 film. The NPMP + can regulate the crystal growth and finally homogenize the grain size and decrease the trap density. Consequently, the LABAs strategy can improve the power conversion efficiency of CsPbTh3 solar cells to 19.02% under 1‐sun illumination (100 mW cm −2 ). Fortunately, the NPMP + and PF6 − ‐treated CsPbTh3 film shows great phase stability after storage in ambient air for 250 days, and the power conversion efficiency of corresponding solar cells is almost 76% of the initial value after 60 days aging under ambient conditions. Abstract : The PF6 − and N ‐propyl‐methyl piperidinium (NPMP + ) within the CsPbTh3 perovskite film form Lewis acid–base adducts to effectively passivate iodide vacancy defects, regulate crystal growth, and finally uniformly improve grain quality and decrease the trap density. This combinational strategy enables the CsPbTh3 perovskite solar cells to achieve high photovoltaic performance and operational stability.